2008
DOI: 10.1080/15376510802442444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aloe Vera Gel on Dermal Wound Healing Process in Rat

Abstract: In this topical study the influence of Aloe Vera, on the wound healing process was investigated in 63 male rats with microscopic and cell count methods. On the day of surgery a round wound, of diameter 20 mm, was created on the back of rats necks under sterile conditions. The surgery day was determined as day zero (0). Then the rats were divided randomly into control and experimental groups 1 and 2. Animals in each group were sub-divided to three smaller groups, investigated every 4, 7, and 14 days. From day 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 11 publications
4
35
0
1
Order By: Relevance
“…vera, known as "the healing plant" (Choi et al, 2001), is effective during healing processes in various tissues. Its effect is described in the literature for fibroblast proliferation, angiogenesis, production of different growth factors, synthesis of ECM components, such as hyaluronic acid, dermatan sulfate and collagen, and increased amount of crosslinks between the collagen molecules, in skin, bone fractures and gastric lesion (Chithra et al, 1998a,b,c;Somboonwong et al, 2000;Rodríguez et al, 2002;Eamlamnam et al, 2006;Prabjone et al, 2006;Habeeb et al, 2007;Takahashi et al, 2009;Takzare et al, 2009;Atiba et al, 2011;Tarameshloo et al, 2012). According to the results of Maia Filho et al (2010), A. vera phonophoresis was effective for the treatment of tendinitis, with reduction of edema and number of inflammatory cells, as well as promoting the recovery of the tensile strength of tendon.…”
Section: Introductionmentioning
confidence: 94%
“…vera, known as "the healing plant" (Choi et al, 2001), is effective during healing processes in various tissues. Its effect is described in the literature for fibroblast proliferation, angiogenesis, production of different growth factors, synthesis of ECM components, such as hyaluronic acid, dermatan sulfate and collagen, and increased amount of crosslinks between the collagen molecules, in skin, bone fractures and gastric lesion (Chithra et al, 1998a,b,c;Somboonwong et al, 2000;Rodríguez et al, 2002;Eamlamnam et al, 2006;Prabjone et al, 2006;Habeeb et al, 2007;Takahashi et al, 2009;Takzare et al, 2009;Atiba et al, 2011;Tarameshloo et al, 2012). According to the results of Maia Filho et al (2010), A. vera phonophoresis was effective for the treatment of tendinitis, with reduction of edema and number of inflammatory cells, as well as promoting the recovery of the tensile strength of tendon.…”
Section: Introductionmentioning
confidence: 94%
“…Among all plant-derived functional foods, aloe products ranked first in health food sales of 2005 in Korea (Park et al 2005). Aloe is widely used in the food product and pharmaceutical industries due to its biological functions of anti-inflammatory activity (Speranza et al 2005), acceleration of wound healing (Takzare et al 2009), and protective effect against liver injury (Arosio et al 2000), although it is not well understood which activity is related to which component.…”
Section: Introductionmentioning
confidence: 99%
“…Aloe is widely used in food products and ranked first in health food sales in 2005 in Korea for its biological function of anti-inflammatory activity [157] and acceleration in wound healing [158]. In a recent study, it was clearly shown that aloe components ameliorate inflammatory responses in a DSS-induced ulcerative colitis rat model [159].…”
Section: Other Complementary and Alternative Medicine (Cam) Modalitiesmentioning
confidence: 99%